Income inequality and the environmental Kuznets curve - Simone Borghesi (Fondazione Eni Enrico Mattei (FEEM), 2000)
This study explores the link between environmental degradation, economic growth and income inequality within the framework of the environmental Kuznets curve (EKC) literature. To investigate this issue, we examine how inequality affects carbon dioxide (CO2) emissions and their relationship with economic growth. We show that the results heavily depend on the specification that one chooses and argue that the fixed-effect (FE) model performs better than the pooled ordinary least squares (OLS) model that has been used in the literature on this subject. Using a FE model we find that inequality has always a statistically non significant impact on CO2 emissions.
Keywords: C23; O13; O15; Q30; 330; Environment; growth; pollution; inequality; Kuznets curve; CO2 emissions; Einkommensverteilung; Wirtschaftswachstum; Umweltbelastung; Luftverschmutzung; Welt; Environmental Kuznets Curve